2020
DOI: 10.5114/pjr.2020.93714
|View full text |Cite
|
Sign up to set email alerts
|

Aftermath of pulmonary tuberculosis: computed tomography assessment

Abstract: PurposePulmonary tuberculosis (PTB) has clinically significant sequelae, even after recommended treatment completion. It is important to recognise these sequelae for accurate assessment of severity and treatment planning, if indicated.Material and methodsWe retrospectively analysed contrast-enhanced computed tomography (CT) scans of chest of 100 patients with previous history of treated pulmonary tuberculosis, excluding those with active pulmonary disease. CT findings were analysed based on parenchymal, airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Usually it is apparent as consolidation in starting phase. 24 In the present study, 66% of patients showed consolidation apart from other characterized appearance. The consolidation links with secondary bronchioles, which forms cavities that are responsible for spreading the disease towards lungs and other important organs of the body.…”
Section: Discussionsupporting
confidence: 51%
“…Usually it is apparent as consolidation in starting phase. 24 In the present study, 66% of patients showed consolidation apart from other characterized appearance. The consolidation links with secondary bronchioles, which forms cavities that are responsible for spreading the disease towards lungs and other important organs of the body.…”
Section: Discussionsupporting
confidence: 51%
“…They categorized the sequelae into parenchymal, airway, pleural, mediastinal, and vascular subtypes. Fibrosis was seen as the most common sequelae in their cohort (11). Menon B et al has described the radiological sequelae in new cases of pulmonary, pleural and mediastinal tuberculosis after they completed their treatment.…”
Section: Discussionmentioning
confidence: 98%
“…TB can affect individuals of all age groups and both sexes, with adult men constituting 56% of all TB cases (Chakaya et al, 2021). TB is a severe infectious pulmonary disorder, resulting in pulmonary consolidation, cavitary lesions, and bronchial wall thickening (Deshpande et al, 2020). Furthermore, COVID-19 patients with active pulmonary tuberculosis face a higher risk of mortality due to compromised lung immunity in comparison to patients without tuberculosis (Aggarwal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%